Efektivitas Ombusdman Republik Indonesia Perwakilan Sulawesi Tengah Dalam Pencegahan Maladministrasi Pelayanan Publik - Triwijaya, Gilang; Tahili, Mashuri H.; Amijaya, Meldi (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to examine the effectiveness of the Ombudsman of the Republic of Indonesia, Central Sulawesi Representative, in handling reports of maladministration in public services. The research uses a descriptive qualitative approach and focuses on the effectiveness indicators proposed by Richard M. Steers, namely productivity, adaptability, job satisfaction, and resource achievement. Data was collected through interviews and documentation. Based on the findings, the productivity indicator is considered fairly good, as seen from the assistants' ability to analyze and follow up on reports adequately, both in terms of speed and accuracy. The informants in this study were selected based on their knowledge of the issues being investigated, including personnel from the Complaint Receipt and Verification Division (PVL), the Report Investigation Division (RIKSA), the Prevention Division, and members of the public who submitted complaints. In terms of adaptability, the performance is also considered good, as the institution has shown the ability to adjust well to changes, both in regulatory aspects and social dynamics. For job satisfaction, employees at the Ombudsman demonstrate a high level of enthusiasm and pride in contributing to the improvement of public service delivery. However, the achievement of performance targets has not been fully optimal, primarily due to a high workload and limited personnel. The findings regarding resource achievement indicate ineffectiveness, as the limited number of staff has resulted in delays in the report examination process, restricted monitoring coverage, and a high individual workload. This issue is a major factor affecting the overall effectiveness of the Ombudsman in carrying out its functions optimally.